Android-Based Accounting Learning Media for Independent Learning for Vocational High School Students - Depi Pramika; Hendri Gunawan; Erma Yulaini (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: This research was created to develop accounting learning media to increase student motivation and learning outcomes and as an alternative learning media for teachers. The media was developed using the Android-based Canva application at SMK N. 8 Palembang. Media development procedures go through validation tests, practical tests, and effectiveness tests on teaching and learning activities and student learning outcomes. Design/methodology/approach: The research method uses development research using 2 development theories, at the development stage using the Rowntree Model and the evaluation stage using Tessmer. Collecting research data using interviews, questionnaires, observations, and tests in the process of design, development, and evaluation. At the stage after developing the learning media prototype the researcher conducted tests involving learning material experts, learning media design experts, and learning media experts to find out the validation of the media that was made. Findings: The results of the validation test of 4.41 were stated to be very valid. Furthermore, a field validation test was carried out on students at SMK N.8 Palembang for each student (one-to-one) and in small groups based on student observations it was found that 100% practicality was very practical. In the final stage of implementing it in a full class by observing student responses using observation, at the end of the lesson a series of tests were carried out to determine the effect of the media on learning outcomes at 85.71% very good criteria. Practical implications: Based on the research, it can be concluded that Android-based accounting learning media has fulfilled the requirements for validity, practicality and has a good potential effect on student learning activities and outcomes. So that Android-based accounting learning media can be used as an alternative teacher in teaching accounting material for adjusting journal entries. Paper type: Research paper